NEGASI DALAM BAHASA IBAN - Maria Magdalena Sinta Wardani; Zhang Huiye (Sintesis, 2016)
This article aims to describe the form and types of negation in the Iban language. The study was conducted in Semunying Jaya, District Jagoi Babang Bengkayang, West Kalimantan during September 2015. The data was collected by observation, interview, record, and notes. The researchers analyze the data by agih method with the basic techniques such as direct dividing element technique and advanced technique of deletion (Sudaryanto, 2015:50). The form of negation in Iban language is formulated and presented informally. The results showed that the negation in the Iban language is a basic form and free morpheme. The word used as a marker of negation is ndak no, ukai not, bedau not yet, nadai none, ngai not want, and anang dont. The type of negation contained in Iban language is the negation assertions, perfective negation, imperfective negation, negation of existence, negative refusal, and negative imperative.Keywords: negation, negative sentences, Iban language